Expression Levels and Clinical Significance of Serum NCAM1 and TTR in Tuberculous Meningitis - Yunhong WU, Shaolong ZHOU, Jing WANG, Yiqiu CAI, Yaming LIN (Zhongguo quanke yixue, 2022)
Background Tuberculous meningitis (TBM) is the most serious type of tuberculosis, usually yielding a high mortality. Antigen detection test in cerebrospinal fluid is the gold standard for etiological diagnosis of TBM, but it may easily lead to delayed treatment due to long culture time (42 days) and high cost. Non-invasive monitoring technologies have demonstrated a wide application prospect, and exploring relevant indicators will help to guide clinical treatment. Objective To investigate the expression levels of serum neural cell adhesion molecule 1 (NCAM1) and transthyretin (TTR) , and their associations with the condition and prognosis of TBM patients. Methods A total of 114 TBM patients〔TBM group, including 31 stage Ⅰ, 45 stage Ⅱ, and 38 stage Ⅲ by the British Medical Research Council (BMRC) staging system〕 were recruited from Sanya People's Hospital and Sanya Central Hospital from March 2017 to December 2020. All of them were treated with anti-tuberculosis therapy and followed up for 1 year after treatment, and their prognosis were classified as good (0-2 points, 63 cases) and poor (≥3 points, 51 cases) by the Modified Rankin Scale. TBM patients were compared to 46 healthy physical examines selected from the two hospitals during the same period in terms of baseline serum NCAM1 and TTR levels. NCAM1 and TTR levels measured at 6 time points (baseline, 7, 14 days after admission, and 1, 6 and 12 months after follow-up) were analyzed, and their associations with as well as predictive values for prognosis in TBM patients were assessed. Results TBM patients had much lower baseline serum NCAM1 and TTR levels than the controls (P<0.05) . Sage Ⅲ TBM patients had notably lower baseline serum NCAM1 and TTR levels than stage Ⅰ and ⅡTBM patients (P<0.05) . TBM patients with poor prognosis had significantly lower serum NCAM1 and TTR levels (measured at each of the aforementioned six time points) than those with good prognosis (P<0.05) . BMRC stage Ⅲ was associated with increased risk of poor prognosis (P<0.05) , while higher baseline levels of serum NCAM1 and TTR were associated with decreased risk of poor prognosis in TBM patients (P<0.05) . For predicting poor prognosis in TBM, the area under the ROC curve of the combination of baseline NCAM1 and TTR was greater than that of baseline NCAM1 (0.879 vs 0.665) or baseline TTR (0.879 vs 0.689) alone (Z=4.428, 3.941, P<0.05) . Conclusion TBM patients were found with decreased serum NCAM1 and TTR levels, which may be associated with their condition and prognosis. BMRC stage Ⅲ may be a risk factor for poor prognosis in TBM.